Experimental study of gas-liquid-sand production behaviors during gas hydrates dissociation with sand control screen - Li, Xiao-Yan; Hu, Heng-Qi; Wang, Yi; Li, Xiao-Sen (Energy, 2022)
Sand production is a great challenge for gas hydrates production, and the use of sand control screen can relieve that. However, the use of the sand control screen could also change the gas/water production behavior, thereby affecting the gas production efficiency. In this study, the experiments of methane hydrate dissociation by depressurization with different mesh sizes of sand control screen (100 mesh, 200 mesh, 300 mesh, and 400 mesh) were conducted in a novel hydrate simulator. The gas-liquid-sand production behaviors during hydrate dissociation with different mesh sizes of sand control screen were analyzed. The experimental results showed that the absence of the sand control screen resulted in an obvious subsidence of the hydrate-bearing sediments due to large amount of sand production. The use of the sand control screen could prevent the sand migration from the hydrate reservoir to the production well, thereby reducing the risk of pipeline blockage and the subsidence of the sediments. The increase of the mesh size of the sand control screen reduced the total amount and the medium particle size of the sand production. However, the existence of the sand control screen also improved the resistance of fluid flowing from the hydrate reservoir to the production well, thereby decreasing the gas production rate. Compared to the average gas production rate without sand control screen, the average gas production rate at depressurization stage (DS) with the sand control screen was reduced by 76-96%. The larger the mesh size of the sand control screen, the greater the flowing resistance. Therefore, it's necessary to combine the sand control effect and gas production rate to select an appropriate mesh size of sand control screen. In this study, the particle size of the quartz sand used to simulate the hydrate-bearing sediments was 200-400 mesh, and the most appropriate mesh size of sand control screen was around 300 mesh. The results of this study are of great significance for developing the sand controlling strategy ...